2017
DOI: 10.1111/bph.14074
|View full text |Cite
|
Sign up to set email alerts
|

Vortioxetine exerts anti‐inflammatory and immunomodulatory effects on human monocytes/macrophages

Abstract: BACKGROUND AND PURPOSEA crosstalk between the immune system and depression has been postulated, with monocytes/macrophages and cytokines having a key role in this interaction. In this study, we examined whether vortioxetine, a multimodal anti-depressive drug, was endowed with anti-inflammatory and antioxidative activity, leading to immunomodulatory effects on human monocytes and macrophages. EXPERIMENTAL APPROACHHuman monocytes were isolated from buffy coats and used as such or differentiated into M1 and M2 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 58 publications
5
42
0
4
Order By: Relevance
“…To this purpose, we measured the effect of serotonin on PMA-induced oxidative burst in human monocytes. As previously shown, 1 mM serotonin reverses the oxidative burst to control values 33 . Known serotonin receptor antagonists ritanserin and ketanserin (10 mM) impaired serotonin action, while pure DGKa inhibitors such as Amb639752 had no effect (Figure 8).…”
Section: Activity Of Compounds On Serotonin Receptorssupporting
confidence: 68%
See 1 more Smart Citation
“…To this purpose, we measured the effect of serotonin on PMA-induced oxidative burst in human monocytes. As previously shown, 1 mM serotonin reverses the oxidative burst to control values 33 . Known serotonin receptor antagonists ritanserin and ketanserin (10 mM) impaired serotonin action, while pure DGKa inhibitors such as Amb639752 had no effect (Figure 8).…”
Section: Activity Of Compounds On Serotonin Receptorssupporting
confidence: 68%
“…Then, cells were stimulated with phorbol 12-myristate 13-acetate (PMA; Sigma-Aldrich, Milano, Italy) 1 mM for 30 min. PMA is a well-known stimulus that induces a strong and significant respiratory burst via PKC activation 33 . Superoxide anion production was then evaluated by the superoxide dismutase (SOD)-sensitive cytochrome C (CytC) reduction assay and expressed as nmoles CytC reduced/10 6 cells/ 30 min, using an extinction coefficient of 21.1 mM.…”
Section: Superoxide Anion (O 22 ) Productionmentioning
confidence: 99%
“…corresponding control. We have previously shown that untreated monocytes do not change marker expression in a two-hour incubation and therefore the untreated control also depicts the baseline expression [36].…”
Section: Surface Marker Expressionmentioning
confidence: 93%
“…The SSRIs, paroxetine and sertraline, have a direct suppressive effect on microglial activation and pro-inflammatory cytokine secretion in mice [ 93 , 94 ]. Talmon et al demonstrated a significant role of alternatively-activated M2-macrophages and its anti-inflammatory effects in the treatment of depressive patients [ 95 ]. In patients taking the prescription drug vortioxetine, an antioxidant, drug treatment stimulated a phorbol 12-myristate 13-acetate (PMA)-induced oxidative burst in monocytes, which polarized the cells from the M1 to the M2 phenotype [ 95 ].…”
Section: Drug Therapeutics Targeting Macrophage Polarizationmentioning
confidence: 99%
“…Talmon et al demonstrated a significant role of alternatively-activated M2-macrophages and its anti-inflammatory effects in the treatment of depressive patients [ 95 ]. In patients taking the prescription drug vortioxetine, an antioxidant, drug treatment stimulated a phorbol 12-myristate 13-acetate (PMA)-induced oxidative burst in monocytes, which polarized the cells from the M1 to the M2 phenotype [ 95 ]. Another group of drugs, nonsteroidal anti-inflammatory drugs (NSAIDs), such as ibuprofen, are oftentimes used in combination with antidepressants.…”
Section: Drug Therapeutics Targeting Macrophage Polarizationmentioning
confidence: 99%